Compact MIMO Antenna for Multiband Mobile Applications - Agrawal, Tanvi; Srivastava, Shweta (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2017)
Abstract This paper presents a multiple input multiple output (MIMO) antenna for multiband operation based on meander lines with L shaped metallic strip. Meander lines is basically a monopole antenna loaded with multiple sections of short circuited transmission line that acts as inductor and alter the impedance characteristics of antenna. Antenna size miniaturization of 69 % has been achieved by placing double U slots on the ground plane and a line slot DGS (Defective Ground Structure) is used to reduce the mutual coupling between the antenna elements. The values of envelope correlation coefficient (ECC) and Specific Absorption Rate (SAR) lie well below the specified limit.